The Relationship between Emotional Intelligence and Perceived Organization Justice among School Counsellors and Social Workers in Sultanate of Oman - Nasra A. Alriyami; Said S. Aldhafri (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The current study aimed to identify the levels of emotional intelligence and perceived organization justice among school counselors and social workers in the sultanate of Oman. In addition, this study aimed to predict perceived organizational justice through emotional intelligence dimension. The study sample consisted of 259 school counsellors and social workers in the Sultanate of Oman. They were chosen in non-probability method. The study utilized a predictive descriptive method. In addition, the study used the Alsmadoni's emotional intelligence scale and Alkhadher et al.'s organization justice scale. The results revealed high levels of emotional intelligence, interactional justice and informational justice. Moderate levels were found for procedural justice and distributive justice. The multiple regression analysis showed the ability of emotional intelligence dimension in predicting procedural justice, and interactional justice, where statistically significant relationships were found between dimensions of self-motivation, social skills and procedural justice. In addition, the dimension of self-motivation was able to predict interactional justice. In contrast, the dimensions of emotional intelligence were unable to predict distributive justice and informational justice.